Avoiding Plagiarism of Students' Scientific Writing by Using the QuillBot Paraphraser - Fitria, Tira Nur (Universitas Lancang Kuning, 2022)
This research reviews the use of QuillBot to paraphrase the students' scientific writing in avoiding plagiarism. This research is descriptive qualitative. Observation is used as the main instrument to collect data. The data uses the app of QuillBot as an object of research. The analysis data use three ways of qualitative analysis, namely reducing data, displaying data, and conclusions. The analysis shows that several ways QuillBot in paraphrasing includes changing the word/phrase/ clause order, using synonyms, changing the sentence structure from active to passive voice, and vice versa, also separating the information into separate sentences. QuillBot Premium contains different modes of paraphrasing depending on writing needs, such as Standard, Fluency, Formal, Simple, Creative, Expand, and Shorten. Standard mode rewrites text reliably to maintain meaning, Fluency mode sure text is readable and free of errors; Formal mode presents the text in a more sophisticated and professional way; Simple mode makes writing more readable and accessible; Creative mode presents the text in a way most people can understand; Expand mode adds more detail and depth to increase sentence length; and Shorten mode strips away extra words to provide a clear message. QuillBot can be used by students to rewrite any writings or as an alternative tool when they cannot paraphrase manually. However, the site is a product of technology. Of course, human intelligence remains the main. Students need to understand in-depth and re-check their writing to get better or higher-quality paraphrasing.